Y > x
y = 2(3+x)
y = 3x-2
------------------------------
2(3+x) = 3x-2
2(3+x) - (3x-2) = 0
6 + 2x -3x + 2 = 0
8 -x = 0
x = 8
---------------------------
y = 2(3+x) = 2(3+8) = 22
y = 3x-2 = 3*8 -2 = 22
----------------------------------
x = 8 ; y = 22
Answer:
substitute that value for x in the polynomial and see if it evaluates to zero
Step-by-step explanation:
A "zero" of a polynomial is a value of the polynomial's variable that make the expression become zero when it is evaluated. As an almost trivial example, consider the polynomial x-3. The value x = 3 is a zero because substituting that value for x makes the expression evaluate as zero.
3 -3 = 0
___
Evaluating polynomials can be done different ways. Straight substitution for the variable is one way. Using synthetic division by x-a (where "a" is the value of interest) is another way. This latter method is completely equivalent to rewriting the polynomial to Horner form for evaluation.
__
In the attachment, Horner Form is shown at the bottom.
Answer:
y = (x/(1-x))√(1-x²)
Step-by-step explanation:
The equation can be translated to rectangular coordinates by using the relationships between polar and rectangular coordinates:
x = r·cos(θ)
y = r·sin(θ)
x² +y² = r²
__
r = sec(θ) -2cos(θ)
r·cos(θ) = 1 -2cos(θ)² . . . . . . . . multiply by cos(θ)
r²·r·cos(θ) = r² -2r²·cos(θ)² . . . multiply by r²
(x² +y²)x = x² +y² -2x² . . . . . . . substitute rectangular relations
x²(x +1) = y²(1 -x) . . . . . . . . . . . subtract xy²-x², factor
y² = x²(1 +x)/(1 -x) = x²(1 -x²)/(1 -x)² . . . . multiply by (1-x)/(1-x)

__
The attached graph shows the equivalence of the polar and rectangular forms.
Answer:
The triangle with those measures will be unique.
Step-by-step explanation:
The triangle described is an isosceles right triangle with side lengths 10 cm. All such triangles are congruent (it is unique).
Answer:

Step-by-step explanation:
Suppose at t = 0 the person is 1m above the ground and going up
Knowing that the wheel completes 1 revolution every 20s and 1 revolution = 2π rad in angle, we can calculate the angular speed
2π / 20 = 0.1π rad/s
The height above ground would be the sum of the vertical distance from the ground to the bottom of the wheel and the vertical distance from the bottom of the wheel to the person, which is the wheel radius subtracted by the vertical distance of the person to the center of the wheel.
(1)
where
is vertical distance from the ground to the bottom of the wheel,
is the vertical distance from the bottom of the wheel to the person, R = 10 is the wheel radius,
is the vertical distance of the person to the center of the wheel.
So solve for
in term of t, we just need to find the cosine of angle θ it has swept after time t and multiply it with R

Note that
is negative when angle θ gets between π/2 (90 degrees) and 3π/2 (270 degrees) but that is expected since it would mean adding the vertical distance to the wheel radius.
Therefore, if we plug this into equation (1) then
